Effect of biological treatment on the daily functioning of patients with rheumatoid arthritis - Miriam Miedziak; Ewelina Bąk; Sylwia Anna Krzemińska (Kazimierz Wielki University, 2017)
Background: Rheumatoid arthritis is an incurable chronic disease which limits the daily functioning of patients in every area of life due to progressive symptoms, the side effects of treatment and frequently occurring severe pain. Material and Methods: The research was carried out using the diagnostic poll method. The research tool applied in the study was an own survey questionnaire together with the Health Assessment Questionnaire (HAQ) included in it. The research was carried out at the Silesian Center for Rheumatology, Rehabilitation and Disability Prevention in Ustroń in the period from 1 st July 2016 to 30th November 2016 among 50 patients. Results: The performed research demonstrated that the majority of patients subjected to biological therapy treatment noticed an improvement of their health status in comparison to the period from before the biological therapy treatment. The biological therapy affected the patients' daily functioning. The HAQ median decreased by 1.50 and the median of pain severity by 47.50, also the morning stiffness was significantly reduced or it did not occur at all. Only a small percentage of respondents continued to report problems with falling asleep or waking up at night. Conclusions: Biological therapy in patients with rheumatoid arthritis bears the desired effects in the form of the improvement of the health status, the reduction of pain severity and the reduction of the occurrence of morning stiffness.